KARAKTERISASI TEPUNG KULIT PISANG DAN UJI DAYA TERIMA TEPUNG KULIT PISANG PADA PEMBUATAN DONAT - Titin Aryani; Isnin Aulia Ulfah Mu’awanah; Aji Bagus Widyantara (IST AKPRIND Yogyakarta, 2018)
Basically, all types of banana peel can be processed into flour, but the best is Raja Banana peel. This study aims to study the character of Raja banana peel flour and test of flour acceptance to the making of donuts. The research method used is quantitative analysis method. Flour characters studied are physical characters and chemical characters. This study also studied the acceptability of banana peel flour on donuts making. Data obtained from the results of laboratory analysis and donut power test results of 60 panelists. Physical character of the banana peel flour studied is the shape, smell, taste, color. Chemical characters studied are antioxidant activity, anthocyanin levels and carotene. The test of banana peel received in the making of donuts is flavor, color, texture and aroma. The results showed that the antioxidant activity of banana flour of Raja was 61.26%, the anthocyanin level was 15.62 mg / 100g, carotene content was 136.61 ppm. Banana flour test of Moses sapientum on making donut with 25% banana peel flour substituents on a scale of 1-5, taste parameter obtained value of 4.37, color 3.36, texture 3,54, aroma 3.68. The conclusion of this research is banana peel flour is relatively effective as substituent of banana peel flour on the making of donut with the amount of substituent as much as 25%. Suggestion of this research is done variation subtituen of Raja banana peel flour on making donut.